PENGARUH METODE CONTEXTUAL TEACHING AND LEARNING ( CTL) PADA MATA PELAJARAN IPA TERHADAP HASIL BELAJAR SISWA KELAS V MI AN-NURONIYAH - Kurniawati Kurniawati; Tohir Solehudin (LPPM Universitas Ibn Khaldun, Bogor, 2020)
This research aims to to increase result of learning at subject of IPA at least reaching KKM ( 70) by using method of Contextual Teaching and Learning that leads students to be active, goodness in cooperating, question and answer, searching answer, explaining and also pay attention to the material described by friends Research type the used of Research Of Action Class ( PTK) classroom action by research conducted by the research of V grade teachers through 3 cycles. Where each cycle is carried out 2 meetings each cycle consisting of four aktivities namely planning,impleminting,observing,evaluatinf, and reflectingPursuant to result of research, reached result in each natural cycle of improvement. In cycle of I percentage of student activity 39,28%. in cycle of II percentage of student activity 85,71%. in cycle of III, percentage of student aktifitas 92,85%. As well as the result of student evaluation each cycle also experience of improvement. in cycle of I only 14 student or 58,33% complete student. In cycle of II there were 19 student or 79,16% complete student. In cycle of III there were 23 student or 95,83% complete student. Based on the results obtained, the can know that applying of method study of Contextual Teaching Learning and can improve result learning IPA outcomes in V grade students MI AN-NURONIYAH This research aims to to increase result of learning at subject of IPA at least reaching KKM ( 70) by using method of Contextual Teaching and Learning that leads students to be active, goodness in cooperating, question and answer, searching answer, explaining and also pay attention to the material described by friends Research type the used of Research Of Action Class ( PTK) classroom action by research conducted by the research of V grade teachers through 3 cycles. Where each cycle is carried out 2 meetings each cycle consisting of four aktivities namely planning,impleminting,observing,evaluatinf, and reflectingPursuant to result of research, reached result in each natural cycle of improvement. In cycle of I percentage of student activity 39,28%. in cycle of II percentage of student activity 85,71%. in cycle of III, percentage of student aktifitas 92,85%. As well as the result of student evaluation each cycle also experience of improvement. in cycle of I only 14 student or 58,33% complete student. In cycle of II there were 19 student or 79,16% complete student. In cycle of III there were 23 student or 95,83% complete student.Based on the results obtained, the can know that applying of method study of Contextual Teaching Learning and can improve result learning IPA outcomes in V grade students MI AN-NURONIYAH